Frequency of occurrence of atmospheric parameters according to AERONET data in Dushanbe - Makhmudov Abduvosit N.; Abdullaev Sabur F.; Maslov Vladimir A. (E3S Web of Conferences)
One of the main factors causing climate and weather changes is dust aerosol in the air. The article analyzes the interannual variation in the occurrence of atmospheric parameters (aerosol optical depth (AOD), water vapor (humidity) content (W) and the Ångström parameter (α), obtained from systematic measurements at the AERONET station in Dushanbe. A comparative analysis of the frequency of occurrence of atmospheric parameters according to AERONET data in the period from 2019 till 2022 years. The main reasons for changes of annual variation of aerosol parameters are meteorological factors, and changes in the dispersed structure of aerosol particles of different origins. The distribution contours of AOD and α have a singlemode character, variations of W are much wider and more diverse and do not have a pronounced form with characteristic contours of occurrence frequency for interannual values of AOD and α. The constructed frequency histograms make it possible to assess the dynamics of atmospheric parameters and predict the state of the entire climate system.